2019
DOI: 10.17533/udea.iee.v37n2e09
|View full text |Cite
|
Sign up to set email alerts
|

Caring during breastfeeding: Perceptions of mothers and health professionals

Abstract: Purpose. To know the perceptions of mothers and health professionals in relation to the care provided and received during breastfeeding at primary health care level.Methods. A qualitative exploratory study was conducted with breastfeeding mothers (10) and primary health care professionals (24). Data was gathered through indepth interviews and focus groups. Data analysis was performed through thematic content analysis. The rigor of the study was ensured by the Guba and Lincoln criteria for qualitative research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
0
10
0
1
Order By: Relevance
“…Entre las principales preocupaciones que surgen en estas personas en relación con Covid-19 se identificó que 257 (73%) informó de que la situación económica y la salud de los miembros de la familia son los aspectos que más les preocupan, la situación del trabajo y su propia salud, equivalentes al 40% y en segundo lugar; 15% de los participantes identifican el estrés como un síntoma que pueden presentar durante esta situación específica; el 10% informa que le preocupa la ocupación del tiempo libre Afecta a la dinámica de las personas, al mundo del trabajo, a la producción tecnológica y genera nuevos hábitos, rutinas y comportamientos, que para muchos pueden ser perjudiciales, comprometiendo la situación sanitaria, especialmente la salud mental, debido al sufrimiento, la incertidumbre, el aislamiento social, la privación y otras lesiones (13) .…”
Section: Descripción De Las Preocupacionesunclassified
“…Entre las principales preocupaciones que surgen en estas personas en relación con Covid-19 se identificó que 257 (73%) informó de que la situación económica y la salud de los miembros de la familia son los aspectos que más les preocupan, la situación del trabajo y su propia salud, equivalentes al 40% y en segundo lugar; 15% de los participantes identifican el estrés como un síntoma que pueden presentar durante esta situación específica; el 10% informa que le preocupa la ocupación del tiempo libre Afecta a la dinámica de las personas, al mundo del trabajo, a la producción tecnológica y genera nuevos hábitos, rutinas y comportamientos, que para muchos pueden ser perjudiciales, comprometiendo la situación sanitaria, especialmente la salud mental, debido al sufrimiento, la incertidumbre, el aislamiento social, la privación y otras lesiones (13) .…”
Section: Descripción De Las Preocupacionesunclassified
“…As such, breastfeeding behaviour is a complex relational event with dynamic interactions between a mother and her child and between this dyad and the family, social and cultural context where they develop. Thus, breastfeeding behaviour goes beyond the personal and interpersonal system and is positioned as a social interaction (Lucchini‐Raies et al., 2019). Social interaction allows women to develop their breastfeeding perceptions not only according to their own emotions and experiences but also in consideration of their families' and other meaningful persons’ experiences around breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…The development phase of the present study was completed previously. It included an umbrella review of the available evidence on the effectiveness of interventions supporting breastfeeding (Lucchini‐Raies & Lopez‐Dicastillo, 2017) and a qualitative study that clarified the relevant key aspects of women's and health professionals' experiences regarding breastfeeding and breastfeeding care (Lucchini‐Raies et al., 2019). The qualitative research revealed that providing and receiving support during breastfeeding is a dynamic and multidimensional experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) For a first-time mother, this transition is more difficult because of not having prior experience. (3) Research findings indicate that first-time mothers require social support during the transition to maternity (4)(5)(6) Social support may be functional and structural. Functional support refers to exchange activities in a relationship and this support is divided -in turn -into informational (information exchanged between individuals or a group, which has a positive result for the recipient), instrumental (transactions in which direct aid or assistance is offered), emotional (emotional concern for the recipient), and of appraisal (statements or expressions of agreement or correction of some action or point of view).…”
Section: Introduction Wmentioning
confidence: 99%